Institutionalizing International Partnership Governance in a Pesantren: A Case Study of the Darunnajah - Al-Azhar University Mabʻūts Program (1986 - 2026) - Sofwan Manaf (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
This study examines the four-decade partnership between Darunnajah Islamic Boarding School (pesantren), Jakarta, and Al-Azhar University, Cairo, through the mabʻūts (delegated-teacher) program from 1986 to 2026, a partnership rarely studied from a management perspective. The objective is to explain the governance structure that sustains the partnership and the mechanisms through which its benefits reach the institution, students, and community. The core problem is why some international partnerships of Islamic institutions endure for decades while others end. Using a single-case study design with document analysis of two memoranda of understanding, foundation archives, and official publications, the study reconstructs twelve assignment periods and analyses the partnership’s governance. The findings show that sustainability rests on three interlocking mechanisms consolidated here as the Institutionalization Contractual Residential Model (IKR Model) namely the institutionalization of the relationship beyond individual figures, a relational contract that clearly allocates responsibilities and dispute-resolution channels, and a three-year residential rotation model that transfers tacit linguistic and ethical knowledge to students. The study offers practical propositions for Islamic institutions seeking to replicate this governance pattern and extends the internationalization and institutional-governance literature to the under-represented pesantren context.